An assessment of the association between political orientation and financial risk tolerance - John E. Grable; Dee Warmath; Eun Jin Kwak (Journal of Risk and Financial Management, 2022)
The purpose of this paper is to present findings from research that was undertaken to answer the following questions. First, to what extent is political orientation associated with financial risk tolerance, and second, to what degree is political orientation predictive of changes in risk tolerance across periods? Using panel collected before and after the 2020 U.S. presidential election, it was determined that the strength of affiliation with the Republican and Democratic Parties was descriptive of cross-sectional financial risk tolerance. Republicans were found to exhibit greater risk tolerance compared with Democrats. Across periods, the risk tolerance of Republicans was less stable, whereas the financial risk tolerance of Democrats was more stable. A significant decrease in risk tolerance was observed for those affiliating as a Republican pre-election to post-election. When political orientation was measured on a scale, the decrease in risk tolerance across periods for Republicans was significant. The risk tolerance of those affiliating as a Democrat increased across the periods but at a lower rate than in the drop in scores among Republicans. When viewed across the variables of interest in this study, political orientation was found to be an important descriptor of FRT.
Keywords: 650; financial risk tolerance; political affiliation; political orientation